Republic of Uganda : Accounting and Auditing - World Bank (Washington, DC, 2012)
This report provides an assessment of accounting and auditing practices within the context of the Uganda institutional framework, to ensure the quality of corporate financial reporting. The accountancy profession in Uganda is young, but growing rapidly. Accounting and auditing practices in Uganda suffer from institutional weaknesses in regulation, compliance, and enforcement of standards and rules. Various weaknesses were identified in the laws and regulations governing financial reporting. Adopting International Accounting Standards (IAS) and International Standards on Auditing (ISA) in 1998 was a positive development. However, full compliance with IAS (and subsequently International Financial Reporting Standards) is not yet readily achieved, and there is inadequate adherence to auditing standards and professional ethics. Apart from the financial institutions and listed companies, monitoring and enforcement mechanisms are ineffective. These factors, as well as inadequate accounting education at university level, lack of learning materials on the international standards, and a lack of monitored and controlled practical training, have contributed to weaknesses in the financial reporting and auditing regime. The policy recommendations in this report focus on improving the statutory framework, strengthening enforcement mechanisms, upgrading professional education and training, and enhancing capacity of regulatory and professional bodies. A major recommendation is the establishment of an independent oversight body. The oversight body will be responsible for adoption, monitoring, and enforcement of IFRS/IAS-based and ISA-based accounting and auditing practices of public interest entities.